Embedding of Selmer group associated to relative Frobenius morphism of an abelian variety into the group of homomorphism of vector bundles - Wu, Z (2022)
In this thesis we show that the Selmer group of the relative Frobenius morphism of an abelian variety defined on the function field of a projective and smooth curve $C$ over a finite field $k_{0}$ of characteristic $p>0$ can be embedded into the group of homomorphisms between two natural vector bundles over $C$.